Establishing sustainable collaborations in global pathology education - Volaric, Ashley K. (Frontiers in Medicine, 2023)
Graduate-level pathology education is under-resourced in low/middle-income countries (LMIC) and provides a unique opportunity for building sustainable collaborations. By focusing on a bi-directional educational exchange through graduate medical training in Pathology and Laboratory Medicine (PALM), global collaborations can extend to research and scholarship efforts. There are few PALM-based graduate medical programs in high-income countries (HIC) that offer this type of global educational exchange, and the few that exist have been mitigated by pandemic-related travel restrictions. Nonetheless, re-investing in these types of exchanges will allow for new opportunity in global pathology education and research for the next generation of trainees. Drawing on the author’s own experience in South Africa and Guatemala, five essential elements to establish a sustainable educational collaboration will be discussed: sustained effort and communication between partners of HIC and LMIC, involvement of key stakeholders, educational curriculum involving community engagement and cultural competency, bi-directional exchange between partners, and dedicated time and funding.